A DFB-LD Internal Temperature Fluctuation Analysis in a TDLAS System for Gas Detection - Yulei Xie; Jun Chang; Xiaohan Chen; Jiachen Sun; Qinduan Zhang; Fupeng Wang; Zhiwen Zhang; Yiwen Feng (IEEE Photonics Journal)
The temperature fluctuations inside commercially distributed feedback laser diode were experimentally measured and analyzed in detail in this study. In tunable diode laser absorption spectroscopy based gas sensing systems, the temperature of the laser source is usually fixed and a current signal is used to drive the laser for wavelength scanning or modulation. Even if the laser is controlled by a robust temperature controller, the internal temperature still fluctuates due to the delayed response of the temperature controller when rapidly changing the drive current. These temperature fluctuations result in distortions in the measured absorption signals which can be effectively suppressed by limiting the drive current modulation to the resonance frequency of the temperature control proportional-integral-derivative loop. This study demonstrates a reduction in the temperature dependent absorption distortions and improves the detection uncertainty using this technique.